TEM STUDY OF THE ALTERATION OF INTERSTITIAL GLASS IN MORB BY INORGANIC PROCESSES - Zhou W.; Peacor D.R.; Alt J.C.; Van der Voo R.; Kao L.S. (My University, 2001)
Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations on a suite of mid-ocean ridge basalts (MORB) reveal abundant interstitial glass, which differs in occurrence and composition from basaltic glass at pillow rims. Interstitial glass consists dominantly of SiO2 and Al2O3 and is depleted in other cations, representing a highly differentiated residual material. Low-temperature alteration by seawater solutions results in the formation of saponite (Mg-rich variety of smectite) replacing the interstitial glass; the Si/Al ratio of this saponite reflects that of the source glass. Chemical changes during this transition differ from those resulting from alteration of basaltic or rhyolitic glass. Alteration of interstitial glass results in uptake of Mg and Fe and loss of Si and Al, but there is little or no leaching of alkalis. This reflects a strong control on chemical reactions by solution composition (high Na and Mg concentrations of seawater fluids). In contrast to basaltic glass at pillow rims, our observations do not reveal microbial activities in the alteration of interstitial glass.
Keywords: MORB; GLASS ALTERATION; CLAY MINERALOGY; TEM